Dissolution behaviors of PuO2(cr) in natural waters - Cho, Hye-Ryun; Cho, Sangki; Kim, Jueun; Han, Sangsoo; Kim, Hee-Kyung; Um, Wooyong (Frontiers in Nuclear Engineering, 2023)
PuO2(cr) dissolution in natural water was investigated at 25 and 60 °C under atmospheric conditions. The concentration of dissolved Pu, [Pudis.], was monitored for 1 year of reaction time. PuO2(cr) dissolution in natural water reached a steady state within 2 months at 25 °C. The [Pudis.] in groundwater and seawater at pH 8 were in the range of [Pudis.] = 0.9–34 and 3.4–27 nM, respectively. The [Pudis.] in concrete porewater (rainwater equilibrated with concrete) at pH 8.1–10.9 was in the range of 0.1–3.2 nM. The [Pudis.] and pH values of groundwater were similar to those of seawater samples having a high ionic strength. The measured [Pudis.] at equilibrium in all natural water samples was between the calculated solubility curves for PuO2(OH)2(am, hyd) and PuO2(am, hyd). Experimental evidence is insufficient to confirm the oxidation state of Pu in solution and solid phases. However, the results of geochemical modeling indicate that PuO2(am, hyd) and aqueous Pu(IV) species are dominant in natural water samples of this work. The dissolution of PuO2 in groundwater decreased at higher temperatures, whereas the influence of temperature in seawater and porewater was not significant under these experimental conditions.